Improvement of Information Technology Infrastructure in Higher Education using IT Balanced Scorecard - Clara Hetty Primasari; Djoko Budiyanto Setyohadi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Today the use of Information Technology (IT) in business is a must since IT is useful to obtain competitive advantage. It can be achieved by alignment of IT and business, which is performed by developing a good IT infrastructure. Higher educational organization is one of business which requires competitive advantage to compete with their competitors. However, there are some problems encountered. These include the lack of a systemic approach to IT implementation, the lack of awareness to use IT, the lack of commitment and the leader's interest to implement IT, the weakness of technical support for IT implementation, poorly targeted staff development, lack of ownership and insufficient funds. Furthermore, an evaluation is need to determine the condition of IT infrastructure problems to deal with issues faced by a higher education organization. Balanced Scorecard is potential framework for analyzing IT infrastructure since it is one of the well-known performance measurements which embrace the important aspect in business. To do performance evaluation in the IT of higher education organization, Balance Scorecard perspective needs to be customized since IT division is more likely to serve internal rather than external parties commonly. The results of this study are expected to give an illustration of the state of IT infrastructure governance of higher education according to four perspectives in IT Balanced Scorecard. Based on this illustration, it can be identified critical recommendation to IT Infrastructure governance in higher education.